Development of anode mixture composition from processing products of coal to produce carbon nanostructures by the plasma-arc method - Старовойт, Анатолий Григорьевич; Кеуш, Лина Геннадьевна; Шмалько, Владимир Михайлович (Technology audit and production reserves, 2015)
It is discussed the use of coal processing products as a part of the anode mixture and their effect on the production of homogeneous carbon nanostructures by the plasma-arc method. The main aim of this research is to develop a theoretical basis and anode mixture composition, allowing to obtain morphologically uniform carbon nanostructures. It was used arc evaporation method for synthesis of nanostructures. Identification of carbon nanostructures and sizes was carried out by electron microscopy. Carbon nanoparticles, carbon filamentary structure and carbon fiber were obtained using the proposed components that make up the anode mixture, pitch coke, coal tar and coal medium temperature pitch. The carbon content in pitch coke and in the form of aromatics in the coal medium temperature pitch may allow to obtain more homogeneous morphologically carbon nanostructure. The research results can be used to improve the strength and corrosion resistance of metals. We propose to use the processing products of coal as part of the anode mixture to produce morphologically uniform carbon nanostructures by the plasma-arc method.